Sub-soil temperature variation and estimation of soil heat flux at Pune - CHOWDHURY, A.; DAS , H. P.; PUJARI, A. D. (MAUSAM, 1991)
Utilising experimental data from 23 November to 8.December 1989. temperature and heat storage variations at Pune have been studied, based on 3 hourly observations.. pattern of penetration of .thermal wave within the soil has been examined and time of occurrence of maximum/minimum temperatures discussed for various depths. Temperature ranges in different layers have been theoretically computed and compared with those based on actual observations. Heat balance at various depths has also been presented and discussed.